PENGARUH PARTISIPASI GENERASI MILENIAL PADA PENCALONAN LEGISLATIF DALAM PILEG DI PROVINSI BALI TAHUN 2019 - Sari Uli, Dini Anasthasia; Erawan, I Ketut Putra; Mahaswari J.M, A.A Sagung Mirah (Jurnal Nawala Politika; 2019, 2019)
ABSTRACT   This study is aimed at determining the existence of millennial generation in participating politics, but at the same time the millennial mostly very apathetic. The purposed of this study is to determine the effect of millennial generation participation in the legislative nomination in Bali Province in 2019, by used the concept of millennial generation, dynasty politics , legislative elections. Q ualitative methods of observation and interviews are used in this study . The results of this study is the participation of millennial generation is influenced the legislating. First, they had influence of elements of political dynasty and also the support of the winning team, secondly, there was no element of dynasty but a winning team, the third, they had a dynasty without winning team, they supported by social media so it makes eas ier to get votes from the millennial .   Key word : Millennial Generation, Political Dynasty, Legislative Nomination.